2015
DOI: 10.15376/biores.10.3.4263-4276
|View full text |Cite
|
Sign up to set email alerts
|

Effect of White Mud as a Second Filler on the Mechanical and Thermal Properties of Bamboo Residue Fiber/Polyethylene Composites

Abstract: The purpose of this study was to investigate the effect of white mud (WM) on mechanical and thermal properties of bamboo plastic composites (BPCs). Bamboo residue fibers (BRFs) and WM were added as the reinforcement, and high-density polyethylene (HDPE) served as the matrix. The lubricating agent and coupling agent were polyethylene wax and maleated polyethylene (MAPE), respectively. The mixture was used to manufacture BPCs using a twin-screw extruder. The crystal structure and thermal properties of BPCs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
0
13
0
1
Order By: Relevance
“…The impact property for the BPCs with different WM content is presented in Figure 5c. As WM particles were unevenly scattered in BPCs, they were unable to effectively terminate fracture initiation and fracture propagation to absorb impact energy when the BPCs were suffering hit from impact force [29,30]. The impact strength of WM-filled BPCs decreased significantly, due to the fact that the micro/nano WM filling effect was poor or hard to fill in tiny gaps of BRF and HDPE, yet they are profoundly incompatible and there were more local stress concentrations generated in the BPCs, so that cracks tend to grow and spread.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact property for the BPCs with different WM content is presented in Figure 5c. As WM particles were unevenly scattered in BPCs, they were unable to effectively terminate fracture initiation and fracture propagation to absorb impact energy when the BPCs were suffering hit from impact force [29,30]. The impact strength of WM-filled BPCs decreased significantly, due to the fact that the micro/nano WM filling effect was poor or hard to fill in tiny gaps of BRF and HDPE, yet they are profoundly incompatible and there were more local stress concentrations generated in the BPCs, so that cracks tend to grow and spread.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has shown that bamboo pulp fiber (BPF) and white mud (WM) significantly improved the mechanical properties of polymer composites [23,24]. Bamboo residue fiber (BRF)-reinforced high-density polyethylene (HDPE) caused the increase of tensile and flexural properties, but BRF-reinforced HDPE had lower impact strength [25]. For this reason, BPF and WM are used to improve the mechanical properties of bamboo plastic composites (BPCs).…”
Section: Introductionmentioning
confidence: 99%
“…Diffraction peaks for UHMWPE‐free bamboo powder/HDPE composites were observed at 2 θ angles of about 21° and 24°, respectively. They corresponded to typical characteristic peaks of (110) and (200) planes, respectively . No new diffraction peaks appeared after the addition of UHMWPE, indicating that the presence of UHMWPE had little effect on the crystal structure of the bamboo powder/HDPE composites.…”
Section: Resultsmentioning
confidence: 95%
“…This could be explained by the fact that due to the incorporation of UHMWPE molecular chains in the composite, the fibers were fully extended, which limited the movement of the HDPE molecular chains. The crystal growth of the HDPE was also limited, so the peak intensity was reduced . The long‐chain lengths UHMWPE fibers also hindered the free movement between the BFs and the HDPE molecules, resulting in decreased crystallinity of the polymer.…”
Section: Resultsmentioning
confidence: 99%
“…Bamboo-plastic composites (BPCs) are manufactured via hot pressing and extrusion or injection moulding using thermoplastics and bamboo instead of wood (Yeh et al 2009;Wu et al 2013). BPCs are widely used in decorations, outdoors, and as non-structural components of buildings (Xian et al 2015) because they are biodegradable, renewable, and environmentally friendly materials (Zhou et al 2015a). However, the interface between the polar, hydrophilic bamboo fibres and the non-polar, hydrophobic low-density polyethylene (LDPE) is weak, which leads to the formation of many gaps and pores between the two materials.…”
Section: Introductionmentioning
confidence: 99%